On mode water formation and erosion in the Arabian Sea: forcing mechanisms, regionality, and seasonality - E. Font; S. Swart; S. Swart; P. N. Vinayachandran; B. Y. Queste (Ocean Science)
Mode water acts as a barrier layer controlling surface-to-interior fluxes of key climatic properties. In the Arabian Sea, mode water stores heat and provides an oxygen-rich layer for rapid remineralization, and its subduction is a direct pathway for oxygen into the upper oxygen minimum zone. We use float observations to characterize the properties of the Arabian Sea mode water layer (MWL). The MWL forms when springtime warming stratifies the surface layer and caps the deep surface mixed layer formed during the winter monsoon. During the summer monsoon, a second MWL is formed south of 20° N following the cessation of wind-driven mixing. We use 1D and 3D models to disentangle the contributions of atmospheric and oceanic forcing to this water mass. The 1D model accurately represents the mode water's formation and erosion, showing that atmospheric forcing is the first-order driver, in agreement with observations. However, there are regions where advective processes, eddy mixing, or biological heating are essential for the formation and/or erosion of the MWL. For instance, in the eastern Arabian Sea, freshwater-driven stratification advected via the West Indian Coastal Current reduces the potential for deep mixed layers via convective mixing, resulting in a thinner MWL. The 3D model shows that the MW contributes 5 ± 1 % to the oxygen content of the upper ocean, with its maximum during spring in the northern Arabian Sea (40 ± 17 %), thus highlighting the key role of the water mass in storing and transporting heat and oxygen to the interior.